자장 구조 변화에 따른 High Power Impulse Magnetron Sputtering (HIPIMS)에서 Al-doped ZnO 박막 증착 특성 - 박동희; 양정도; 최지원; 손영진; 최원국 (한국재료학회, 2010)
In this study characteristics of Al-doped ZnO thin film by HIPIMS (High power impulse sputtering) are discussed. Deposition speed of HIPIMS with conventional balanced magnetic field is measured at about 3 nm/min, which is 30% of that of conventional RF sputtering process with the same working pressure. To generate additional magnetic flux and increase sputtering speed, electromagnetic coil is mounted at the back side of target. Under unbalanced magnetic flux from electromagnet with 1.5A coil current, deposition speed of AZO thin film is increased from 3 nm/min to 4.4 nm/min. This new value originates from the decline of particles near target surface due to the local magnetic flux going toward substrate from electromagnet. AZO film sputtered by HIPIMS process shows very smooth and dense film surface for which surface roughness is measured from 0.4 nm to 1 nm. There are no voids or defects in morphology of AZO films with varying of magnetic field. When coil current is increased from 0A to 1A, transmittance of AZO thin film decreases from 80% to 77%. Specific resistance is measured at about 2.9 × 10-2 Ω·cm. AZO film shows C-axis oriented structure and its grain size is calculated at about 5.3 nm, which is lower than grain size in conventional sputtering.